PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN INFORMASI PENGENDALIAN INTERNAL - Muhammad Dzulfahmi Ismail; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2017)
This study aims to examine the influence of corporate governance mechanisms on internal control information disclosure. Corporate governance mechanisms that are used in this study are ownership concentration, board of commissioner independence, institutional ownership, board of commissioner size, and external auditor size. This study also uses some corporate characteristics that are predicted to have influence on internal control information disclosure as control variables. The population in this study is non-financial companies that are listed on Main Board of Indonesia Stock Exchange in 2014 and 2015. The sampling method in this study is purposive sampling method. Based on sample selection, 163 companies are selected as sample of this study. Multiple regression analysis is used to analyze data in this study. The results showed that ownership concentration and board of commissioner size have significant positive effect on internal control information disclosure. Board of commissioner independence has significant negative effect on internal control information disclosure. Institutional ownership and external auditor size do not have significant effect on internal control information disclosure.